Prevalence of obstetrical disorders in dairy cows of northern Bangladesh - Sarder, Md Jalal Uddin; Uddin, Jashim; Islam, Md Hemayatul; Islam, Md Reazul (Asian Journal of Medical and Biological Research, 2015)
The study was conducted to investigate the prevalence of obstetrical disorders (ODs) of 975 dairy cows in relation to genotype, age, parity, housing system, feed quality, rearing system, breeding systems and professional training of owners at Rajshahi, Bangladesh from the period 1 January, 2009 to 31 December, 2009. Extensive survey was conducted in 15 areas of Rajshahi and in each area 65 dairy cows were selected randomly. Individual farmers were interviewed to obtain information about ODs of dairy cows viz; abortion, dystocia, retained placenta, uterine and vaginal prolapse. Out of 975 cows, 117 animals were found to be affected by various ODs showing an overall prevalence of 12.00%. Among the ODs, retained placenta showed the highest prevalence (4.10%) followed by abortion (4.0%), dystocia (2.77%), uterine prolapse (0.66%) and vaginal prolapse (0.51%). The observation of genotype wise ODs in cows revealed that the maximum prevalence was in the Local × Friesian (15.97%), followed by Local (14.68%) and Local × Jersey (9.80%) while the minimum prevalence was in the Local × Sahiwal (5.55%). The age group (>48 months) showed highest prevalence (20.25%) of ODs while the lowest (6.66%) was recorded in < 24 months of age in cows. Parity-wise splitting of the data showed that the maximum prevalence of ODs was in the >5th parity (15.35%) and minimum in the 1st parity (6.15%) of cows. The traditional rearing and farming system revealed highest (17.26%) and lowest (8.51%) prevalence of ODs in cows, respectively. The quality of feed had effect on prevalence of ODs in dairy cows (P<0.05). The ODs were also increased in artificial inseminated cows (12.59%) than naturally service groups (11.90%). The training of farmers had significant effect among the non trained and trained groups for the occurrence of ODs in cows. The study revealed relatively low prevalence of reproductive disorders in cows at Rajshahi compare to other regions of Bangladesh, might be due to better management practices adopted by the farmers and efficient veterinary services as well as awareness among farmers. Asian J. Med. Biol. Res. June 2015, 1(2): 216-221